Explanations of news personalisation across countries and media types - Mariella Bastian; Mykola Makhortykh; Jaron Harambam; Max van Drunen (Internet Policy Review, 2020)
News outlets worldwide increasingly adopt user- and system-driven personalisation to individualise their news delivery. Yet, the technical implementation of news personalisation systems, in particular the one relying on algorithmic news recommenders (ANRs) and tailoring individual news suggestions with the help of user data, often remains opaque. In our article, we examine how news personalisation is used by quality and popular media in three countries with different media accountability infrastructures - Brazil, the Netherlands, and Russia - and investigate how information about personalisation usage is communicated to the news readers via privacy policies. Our findings point out that news personalisation systems are predominantly treated as black boxes that indicate a significant gap between practice and theory of algorithmic transparency, in particular in the non-EU context.
Keywords: 300; News personalisation; Privacy policies; Transparency; Accountability; Comparative journalism research